2021
DOI: 10.1108/lht-09-2020-0224
|View full text |Cite
|
Sign up to set email alerts
|

Research output of Indian universities in sciences (2015–2019): a scientometric analysis

Abstract: PurposeThe present study aims to trace out the science research output of top Indian universities from 2015 to 2019, as reflected in the Web of Science (WOS) database.Design/methodology/approachThe present study has selected the Science Citation Index (SCI) of WOS core collection for selecting top Indian universities in terms of total publications in the last five years (2015–2019). The University of Delhi (DU), Banaras Hindu University (BHU), Anna University (AU), Jadavpur University (JU) and Punjab Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…The wide acceptance of this database has prompted the present study to use Scopus as a research database to execute quantitative bibliometric analysis in line with the identified study objectives. Further to expedite bibliometric network analysis, VOSviewer and RStudio tools were applied for taking a holistic visualisation approach in line with the study objectives (Mahala and Singh, 2021; Guleria and Kaur, 2021). The timeframe of the study for retrieving the academic publications from the Scopus database is a decade i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The wide acceptance of this database has prompted the present study to use Scopus as a research database to execute quantitative bibliometric analysis in line with the identified study objectives. Further to expedite bibliometric network analysis, VOSviewer and RStudio tools were applied for taking a holistic visualisation approach in line with the study objectives (Mahala and Singh, 2021; Guleria and Kaur, 2021). The timeframe of the study for retrieving the academic publications from the Scopus database is a decade i.e.…”
Section: Methodsmentioning
confidence: 99%
“…They noted that India's publications on planetary science research have increased over time, with an annual growth rate of 9.66%, and the USA was the primary collaborator with India. Readers may also be interested in Mahala and Singh (2021), who traced the science research output of top Indian universities from 2015 to 2019. Yang and Qi (2020) compared the impacts of proceedings papers in the fields of social SSH and science.…”
Section: Studies On Education and Culturementioning
confidence: 99%
“…This selection consists of bibliometric, scientometric and related analyses on several interesting topics. Articles cover the application of these analyses on research outputs related to Alzahra University in Iran (Doulani, 2021), Iranian clinical medicine researchers (Batooli et al, 2021), a group of five top Indian universities in science (Mahala and Singh, 2021), and China's international collaborative research projects funded by the National Natural Science Foundation of China (Chen et al, 2021b). We also include studies on using these techniques in studying the use of Sci-Hub in research (Behboudi et al, 2021), ecopreneurship (Guleria and Kaur, 2021), as well as the current research trends in 5G security (Farooqui et al, 2021).…”
Section: Special Selection Of Bibliometric and Literature Reviewmentioning
confidence: 99%